Fabrication of diisopropylammonium bromide aligned microcrystals with in-plane uniaxial polarization. (14th November 2016) - Poddar, Shashi; Lu, Haidong; Song, Jingfeng; Goit, Om; Valloppilly, Shah; Gruverman, Alexei; Ducharme, Stephen
Abstract: Textured arrays of ferroelectric microcrystals of diisopropylammonium bromide were grown from solution at room temperature onto silicon substrates and studied by means of x-ray diffraction, atomic force microscopy, electron microscopy, and piezoresponse force microscopy. The needle-shaped crystals had dimensions of approximately 50 µ m × 5 µ m in the plane and were approximately 200 nm thick, where the dimensions and arrangement were influenced by growth conditions. The observations suggest an Ostwald ripening mechanism of the microcrystal growth. The crystals had the structure of the ferroelectric phase, where the polarization axis was in-plane and parallel to the long axis of the crystals. The in-plane polarization could be switched at will with a scanning probe tip bias of 15 V and could be arranged in stable domain patterns with both charged and uncharged 180° domain walls.